Hiatal hernia surgery: laparoscopic versus robotic approach? - R. N. Komarov; S. V. Osminin; I. R. Bilyalov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Evaluate the advantages and disadvantages of laparoscopic and robot-assisted anti-reflux operations.General findings. Reflux esophagitis in the association with hiatal hernia on the third place in the structure of gastroenterological diseases. The development of minimally invasive surgical technologies has led to an increase in the number of laparoscopic and robot-assisted anti-reflux operations. The literature review includes 12 studies, the results of which were published from 2002 to 2020, with a total number of patients 1633. In most of them, when comparing laparoscopic and robot-assisted anti-reflux operations, the advantages of one or another technique were not revealed. In some studies, the high cost and duration of the operation were noted when using the da Vinci robotic surgical complex. Other studies have reported possible improvements in the treatment outcomes of patients with large or recurrent hiatal hernias due to the high precision of movement and improved visualization characteristic of therobot-assisted surgeries.Conclusion. It is necessary to conduct more researches on this problem to develop indications for the choice of a particular surgical approach, as well as to create a single transparent algorithm for the surgical treatment of patients with reflux esophagitis and hiatal hernia.